2021
DOI: 10.1038/s41598-021-91617-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insight into COF monolayers for urea sorption in artificial kidneys

Abstract: Urea removal from an aqueous solution is considered a challenge in the biological process. The state of complete kidney destruction is known as an end-stage renal disease (ESRD). Kidney transplant and hemodialysis are the most common methods for confronting ESRD. More recently, wearable artificial kidney (WAK) devices have shown a significant improvement in urea removal performance. However, low efficiency in physical adsorbents is a barrier in developing them. For the first time, the urea adsorption capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Considering the polarity of selected pharmaceutical pollutants, physisorption can occur through hydrogen bonding and dipole interaction. Note that apart from the existence of electronegative atoms, the spatial coordination of atoms in terms of both the angle (less than 30°) and distance (less than 3.5 Å) should be appropriate Table demonstrates the average number of H-bonds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the polarity of selected pharmaceutical pollutants, physisorption can occur through hydrogen bonding and dipole interaction. Note that apart from the existence of electronegative atoms, the spatial coordination of atoms in terms of both the angle (less than 30°) and distance (less than 3.5 Å) should be appropriate Table demonstrates the average number of H-bonds.…”
Section: Resultsmentioning
confidence: 99%
“…We employed an umbrella sampling technique to compute Gibbs free energy, as Jahromi et al described previously. Briefly, a particular pharmaceutical pollutant molecule, which has been attached to the adsorbent during the simulation, is separated by 6 nm using the pull code method, in which 100 distinct configurations are extracted to calculate the Gibbs free energy.…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jahromi et al used molecular dynamics methods to study the adsorption of urea in five different types of covalent organic frameworks (COFs). 22 The authors reported that imine-linked COF (TPA-COF) exhibits the highest adsorption capacity of urea. Maleki et al computationally investigated the removal of urea and creatinine from 2D materials such as metal carbides, MXenes, MBenes, and COFs using simulation methods such as molecular dynamics and density functional theory.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular dynamics (MD) method has been widely used in the simulation of two-dimensional materials such as graphene [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. For example, in terms of mechanical properties, Ni et al [ 26 ] studied the anisotropic mechanical properties of graphene sheets by using the MD method.…”
Section: Introductionmentioning
confidence: 99%